History of Babul Mukarramah and The White Robe Movement in the New Order Era - Asmanidar Asmanidar; Khairil Fazal (UIN Sumatera Utara Medan, 2022)
The White Robe Movement, a very brave heroic movement of santri dayah, was pioneered by aceh's charismatic ulama, Teungku Bantaqiah a leader of the Salafist dayah (Babul Mukarramah), Beutong Ateuh region. The purpose of this movement is to prevent various kinds of rampant toxicity in Aceh during the New Order era. This movement was inspired by the process of studying in depth the practice of Sufism and the order taught in Babul Mukarramah's father, namely the muqarabah and mujahadah methods. This method has been able to seep into the souls of the students who are applied through jihad in the way of Allah Almighty. This study aims to explain the history of Babul Mukarramah and The White Robe Movement. Data collection is carried out in four ways, namely by observation, literature studies, document studies, and interviews. The methods used are historical methods and qualitative approaches. The results of data analysis showed that The White Robe Movement only developed around 1987, besides it was named because of the vision and mission. The movement, led directly by Teungku Bantaqiah, is just a group of students who want to convey their aspirations regarding the government's policy of insurgent Aceh and leaving the Acehnese people in a backwardness and downturn.